Efficient Green Synthesis of Imidazo[2,1-b]thiazol-5-yl-2,4-dihydropyrano[2,3-c]pyrazole Derivatives Using HPA-Montmorillonite-KSF - Kushwaha, Pragati; Bhardwaj, Ayush; Rashi, Rashi; Khan, Danish; Gupta, Maneesh Kumar (Synlett, 2025)
Herein, we developed a simple, efficient, cost-effective, recyclable, and green approach for synthesizing imidazo[2,1-b]thiazol-5-yl-2,4-dihydropyrano[2,3-c]pyrazole derivatives. The reaction protocol involves ‘HPA-montmorillonite-KSF’ as a reusable and heterogeneous catalyst and proceeds via multicomponent reaction (MCR). Various substituted imidazo[2,1-b]thiazol-5-yl-2,4-dihydropyrano[2,3-c]pyrazole derivatives were prepared in good to excellent isolated yields. This methodology is compatible with the gram-scale synthesis and provides an efficient and much improved modification of the original MCR, considering the yield and mild reaction conditions.
Keywords: montmorillonite; catalysis; green synthesis; imidazo[2,1-b]thiazole; pyrano[2,3-c]pyrazole